2020
DOI: 10.1016/j.actamat.2019.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation density distribution at slip band-grain boundary intersections

Abstract: We study the mechanisms of slip transfer at a grain boundary, in titanium, using Differential Aperture X-ray Laue Micro-diffraction (DAXM). This 3D characterisation tool enables measurement of the full (9-component) Nye lattice curvature tensor and calculation of the density of geometrically necessary dislocations (GNDs). We observe dislocation pile-ups at a grain boundary, as the neighbour grain prohibits easy passage for dislocation transmission. This incompatibility results in local micro-plasticity within … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…In plastically deformed alloys [5], a larger number of deformation bands (DBs), that can effectively accommodate the plastic strain and give rise to the heterogeneities in microstructure, are observed and well explained in our previous work [25]. Furthermore, a higher magnitude of dislocation density is found near the grain boundaries due to the prohibition of dislocation transmission from the neighbouring grain [26,27]. Hence, both DBs and grain boundaries could be the possible nucleated sites for RX [2,18].…”
Section: Introductionsupporting
confidence: 75%
“…In plastically deformed alloys [5], a larger number of deformation bands (DBs), that can effectively accommodate the plastic strain and give rise to the heterogeneities in microstructure, are observed and well explained in our previous work [25]. Furthermore, a higher magnitude of dislocation density is found near the grain boundaries due to the prohibition of dislocation transmission from the neighbouring grain [26,27]. Hence, both DBs and grain boundaries could be the possible nucleated sites for RX [2,18].…”
Section: Introductionsupporting
confidence: 75%
“…These values are listed in Table 1. Despite the limitations of the technique, Guo et al (2020) showed that GND densities obtained minimizing the total line energy of the 2D lattice curvature tensor correlate well with 3D GND density measurements obtained by Differential Aperture X-ray Laue Micro-diffraction, which enables the measurement of the full (9-component) Nye lattice curvature tensor. Thus, the present method provides relative values of the GND density proportional to the misorientation whenever the latter is higher than the angular resolution of the EBSD system.…”
Section: Determination Of the Dislocation Types Composing The Subgrains Walls (Labs)mentioning
confidence: 83%
“…Despite the limitations of the technique, Guo et al (2020) showed that GND densities obtained minimizing the total line energy of the 2D lattice curvature tensor correlate well with 3D GND density measurements obtained by Differential Aperture X-ray Laue Micro-diffraction, which enables the measurement of the full (9-component) Nye lattice curvature tensor. Thus, the present method provides relative values of the GND density proportional to the misorientation whenever the latter is higher than the angular resolution of the EBSD system.…”
Section: Determination Of the Dislocation Types Composing The Subgrains Walls (Labs)mentioning
confidence: 83%